2015
DOI: 10.5301/jbm.5000121
|View full text |Cite
|
Sign up to set email alerts
|

Biased Paternal Transmission of TRH Variant to Female down Syndrome Probands: Possible Correlation with Low Breast Cancer Frequency

Abstract: Thyroid malfunction is more common in individuals with Down syndrome (DS) than in the general population. It has been hypothesized that thyroid may influence cancer risk. Individuals with DS are at greater risk of developing leukemia than the general population, while solid tumors especially breast cancer (BC) are rare. BC patients have higher levels of circulating thyroid-stimulating hormone (TSH) and prolactin (PRL), both regulated by the thyrotropin-releasing hormone (TRH), a hypothalamic tripeptide. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Since some physiological abnormalities like, cognitive impairment, growth retardation, muscle hyporonia, lethargy, dullness, as well as large tongue with underdeveloped nasal bridge and short neck are observed in subjects with DS as well as those with irregular thyroid functions, we speculated that abnormal function of the thyroid gland, due to defects in genes encoding for proteins involved in thyroid hormone (TH) synthesis, secretion, or recycling, may have a role in DS related thyroid abnormalities. Our preliminary investigation revealed that the thyrotropin releasing hormone (TRH) gene variant, rs13097335 "G" allele, in addition to having lower occurrence in the BC population than female control, was preferentially transmitted from parents to female DS probands and based on the observation we hypothesized that higher occurrence of rs13097335 "G" allele in female DS probands may confer protection to BC [18]. In the present study, we investigated two other TH biosynthesis pathway genes, Solute carrier family 5 member 5 (SLC5A5) or NIS [19] and thyroid peroxidase (TPO) [20,21], in nuclear families with DS probands to find out their role.…”
Section: Journal Of Down Syndrome and Chromosome Abnormalitiesmentioning
confidence: 99%
“…Since some physiological abnormalities like, cognitive impairment, growth retardation, muscle hyporonia, lethargy, dullness, as well as large tongue with underdeveloped nasal bridge and short neck are observed in subjects with DS as well as those with irregular thyroid functions, we speculated that abnormal function of the thyroid gland, due to defects in genes encoding for proteins involved in thyroid hormone (TH) synthesis, secretion, or recycling, may have a role in DS related thyroid abnormalities. Our preliminary investigation revealed that the thyrotropin releasing hormone (TRH) gene variant, rs13097335 "G" allele, in addition to having lower occurrence in the BC population than female control, was preferentially transmitted from parents to female DS probands and based on the observation we hypothesized that higher occurrence of rs13097335 "G" allele in female DS probands may confer protection to BC [18]. In the present study, we investigated two other TH biosynthesis pathway genes, Solute carrier family 5 member 5 (SLC5A5) or NIS [19] and thyroid peroxidase (TPO) [20,21], in nuclear families with DS probands to find out their role.…”
Section: Journal Of Down Syndrome and Chromosome Abnormalitiesmentioning
confidence: 99%